Enlightenment and Republic in Simón Rodríguez Polítical Thought - Rosales Sánchez, Juan José (Res Publica. Revista de Historia de las Ideas Políticas, 2018)
This paper examines the influence of the Enlightenment on the work of Simon Rodriguez, especially in his republican thought. According to him, in the early nineteenth century of South America the consolidation of republic is built up in two stages. The first one has been accomplished: independence, a military achievement; the second, freedom, that was about to unfold. On this second phase, he believes that it can only be carried out if citizen is taught, and for tackling that out republican education is indispensable. Thus, this philosopher considers the best option for the republic foundation goes through the application of some of the Enlightenment political, social and educational ideas.
Keywords: Illustration; Independence; Freedom; Republican Thought; Simon Rodríguez.